Refined analysis of transcranial Doppler HITS - Hennerici, Michael G.; Meairs, Stephen (The lancet, 2002)
Transcranial Doppler is used in several specialised centres to detect microembolic - signals in the cerebral circulation. This technique, which was first reported almost - two decades ago,1 may benefit patients who are at increased risk during interventional - investigations and carotid surgery.2 To detect microembolic signals a Doppler probe - with a frequency of approximately 2 MHz is fixed over the temporal bone—its position, - orientation, and the Doppler sample volume depth are adjusted to obtain a good signal - from the ipsilateral middle cerebral artery.
Gesehen am 26.03.2021